Development of operator training simulator using aspen simulation workbook (ASW): a reactor case study - Farah Syahirah, Yahya (2015)
Operating Training Simulator (OTS) is a computer-based training system. The OTS applies a simulation of an industrial process to generate the appropriate data of the plant‟s process operation. In addition, the OTS is widely accepted in the industry as an enabling technology for employee competency and proficiency training and enhancement. This system is deemed as the effective application in order to develop the highest skill levels and proficiency of the operator. This project presents the first-hand experience of developing a process simulator system using Aspen Simulation Workbook (ASW). The production of acetic acid from methanol carbonylation is used as a case study. Aspen Plus is used for the modelling of the methanol carbonylation process and will be linked with Excel using Aspen Simulation Workbook. The simulation can be operated in Aspen Simulation Workbook by manipulating the value of the variables. This case study is about to determine the changes of output variable by manipulates the input variables. This would contribute towards the solution of training issues related to control and operate a process and act as a tool to educate and train the engineering students for supporting training in control and operate certain processes respectively. The operator training tool is developed successfully in Aspen Simulation Workbook.